Enabling 4-Lane Based 400 G Client-Side Transmission Links with MultiCAP Modulation. (11th August 2015) - Tatarczak, Anna; Iglesias Olmedo, Miguel; Zuo, Tianjian; Estaran, Jose; Bevensee Jensen, Jesper; Xu, Xiaogeng; Tafur Monroy, Idelfonso
Abstract : We propose a uniform solution for a future client-side 400 G Ethernet standard based on MultiCAP advanced modulation format, intensity modulation, and direct detection. It employs 4 local area networks-wavelength division multiplexing (LAN-WDM) lanes in 1300 nm wavelength band and parallel optics links based on vertical cavity surface emitting lasers (VCSELs) in 850 nm wavelength band. Total bit rate of 432 Gbps is transmitted over unamplified 20 km standard single mode fiber link and over 40 km link with semiconductor optical amplifier. 70.4 Gb/s transmission over 100 m of OM3 multimode fiber using off-the-shelf 850 nm VCSEL with 10.1 GHz 3 dB bandwidth is demonstrated indicating the feasibility of achieving 100 Gb/s per lane with a single 25 GHz VCSEL. In this review paper we introduce and present in one place the benefits of MultiCAP as versatile scheme for use in a number of client-side scenarios: short range, long range, and extended range.